2019
DOI: 10.1002/hon.2676
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐body magnetic resonance imaging (WB‐MRI) in lymphoma: State of the art

Abstract: The improvements in magnetic resonance imaging (MRI) technology and the concern related to the increased cancer risk in patients with lymphoma, also due to radiation exposure associated with imaging examinations, have led to the introduction of whole‐body MRI (WB‐MRI) as a radiation‐free alternative to standard imaging procedures. WB‐MRI seems a less histology‐dependent functional imaging test than 18F‐fluorodeoxyglucose‐positron emission tomography/CT (18F‐FDG‐PET/CT). In patients with FDG‐avid lymphomas, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 85 publications
1
20
0
1
Order By: Relevance
“… 13 , 14 In malignant lymphoma, MRI demonstrates T2 high intensity with Gd enhancement and a decrease in ADC. 15 , 16 For the diagnosis of uterine relapse of ALL, MRI was effective in two previously reported cases and ours, and its common findings, i.e., T2 high intensity with Gd enhancement and the marked decrease in ADC, may be useful to differentiate the lesion from primary uterine cancer.…”
Section: Discussionmentioning
confidence: 52%
“… 13 , 14 In malignant lymphoma, MRI demonstrates T2 high intensity with Gd enhancement and a decrease in ADC. 15 , 16 For the diagnosis of uterine relapse of ALL, MRI was effective in two previously reported cases and ours, and its common findings, i.e., T2 high intensity with Gd enhancement and the marked decrease in ADC, may be useful to differentiate the lesion from primary uterine cancer.…”
Section: Discussionmentioning
confidence: 52%
“…The diagnostic value of WB-MRI has been established in the evaluation of solid tumors, such as lung cancer, hematologic malignancy (multiple myeloma and aggressive lymphoma), and bone metastasis, compared to 18 F-FDG-PET/CT [9][10][11][12][13][14][15]28]. With regard to evaluating and monitoring indolent lymphoma, WB-MRI has been considered a reasonable option under the watchful waiting strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The role of whole-body magnetic resonance imaging (WB-MRI) has been well established in hematologic malignancies and multiple metastases, especially with regard to the evaluation of bone involvement in these diseases [8][9][10][11][12][13][14][15]. However, relatively little information exists on its utility for the evaluation of indolent lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Whole Body Diffusion MRI (WB-DW MRI) has been proposed as a possible alternative to PET/CT [25,26]. It has also been demonstrated that WB-DW MRI is less histology dependent than PET/CT and thus is likely to become the imaging test of choice for staging indolent lymphomas with low FDG avidity in a short time frame [27][28][29].…”
Section: Discussionmentioning
confidence: 99%